Investigating the Features of Sales Promotions: Conceptualization and Empirical Evidence - Simamora, Bilson; Xzyfanequo, Syanne Emmanuella (International Review of Management and Marketing, 2024)
Amid the tight competition and subtle differences between the available options, sales promotion has become an important marketing strategy, primarily for e-commerce companies. However, the fast development leaves the sales promotion concept behind. Specifically, the academicians have not reached a solid conclusion about sales promotion features. This study aims to unify the scattered features of sales promotion tools and demonstrate the direct or indirect influence of chosen techniques on behavioral intention. The study identifies six features of sales promotion tools, and they influence consumer behavior directly or indirectly through attractiveness, following the comprehension and non-comprehension models. Future researchers could investigate the joint effect of features, tools, and companies on consumer behavior.